A synthesis of human conflict with an African megaherbivore; the common hippopotamus - van Houdt, Shaya; Traill, Lochran W. (Frontiers in Conservation Science, 2022)
The common hippopotamus is an extant African megaherbivore that is relatively understudied by scientists and underfunded by conservation organisations. Conflict with people, however, is a major concern given the danger that hippo pose to human life. Moreover, very little is known about human hippo conflict (HHC) and experimental fieldwork on mitigation methods have hardly been conducted. Here we conduct an exhaustive review of the primary and grey literature outlining how conflict between people and hippo arises, the impacts of conflict on both human communities and hippo populations, and all known intervention measures. Our review highlights the effectiveness of barriers around crops, riparian buffer zones (that exclude cattle and crop planting), and payments for environmental services as tools to mitigate HHC. This study also highlights the knowledge gaps in HHC research; particularly the spatial scale of HHC, the lack of field experimental research on deterrents and a paucity of knowledge on outcomes of projected climate change and HHC.